Effect of tractor forward speed and type of transmission system on agricultural tractors performance under clay soil condition - A, 1Mohamed; D. Elfadil, 2Abdelkarim; Muhieldeen, Osama A. (Gezira Journal of Engineering and Applied Sciences, 2019)
This research study was conducted at the Experimental Farm of the University of Gedarif during the season 2016/ 2017 to evaluate the effect of forward speed and type of transmission system on some performance parameters of agricultural tractors. The transmission systems used were the conventional, powershift and a combination of conventional and powershift. The tested parameters were the drawbar power, fuel consumption, field capacity and wheel slippage at three levels of speed of 5, 6 and 7 km/hr. A completely randomized block design with three replications was used to execute the experiment. The results of the experiment showed that, there was a significant difference in the drawbar power between conventional and the other two systems for the speed of 5km/hr, it gave about 20kW lower drawbar power. No significant difference between the three systems for the speeds of 6 and 7 km/hr. For the speed of 5km/hr there was no significant difference (p ≥0.05) between conventional and powershift transmission systems in fuel consumption, while the combination showed the highest fuel consumption. For the speed of 6km/hr the combination showed the lowest fuel consumption. No significant difference between the three systems for the speed of 7km/hrThis referred to the variation of engine revolution per minute and the gear ratio for each type of tractor to achieve the required speeds. Regarding field capacity, there was no significant difference between the powershift and the combination systems at 5km/hr. For the speed of 6km/hr there was no significant difference between the three systems. For the speed of 7km/hr there was a significant difference between the combination and the other two systems. The combination gave the highest field capacity. The statistical analysis illustrated that there was no significant differences (p ≥0.05) between the three tractors for the speed of 5km/hr and 6km/hr. No significant difference between powershift and combination tractors for the speed of 7km/hr, while there was a significant difference between the conventional and the other two systems for the speed of 7km/hr.